Antibacterial and antibiofilm activities of silver-decorated zinc ferrite nanoparticles synthesized by a gamma irradiation-coupled sol–gel method against some pathogenic bacteria from medical operating room surfaces. Issue 45 (23rd August 2021) - Abdel Maksoud, M. I. A.; El-Sayyad, Gharieb S.; El-Bastawisy, Hanan S.; Fathy, Rasha M.
Abstract : This work aimed at the gamma irradiation-assisted synthesis of silver (Ag)-decorated ZnFe2 O4 (ZFO) ferrite nanoparticles (NPs), which were tested for their antibacterial and antibiofilm activities against some pathogenic bacteria from medical operating room surfaces. Abstract : This work aimed at the gamma irradiation-assisted synthesis of silver (Ag)-decorated ZnFe2 O4 (ZFO) ferrite nanoparticles (NPs), which were tested for their antibacterial and antibiofilm activities against some pathogenic bacteria from medical operating room surfaces. The prepared Ag-decorated ZFO NPs were characterized via XRD, SEM, EDX, elemental mapping, and FTIR analysis. The antibacterial potential was tested as ZOI and MIC, while antibiofilm activity was estimated by the tube method. The growth curve assay, the effect of UV on the antimicrobial activity, and cell membrane leakage were evaluated, and the antibacterial reaction mechanism was investigated by SEM/EDX analysis. The XRD and FTIR results confirmed the successful preparation of Ag-decorated ZFO NPs. Antibacterial results revealed that the most potent decorated sample was Ag0.75 @ZFO NPs, recording the most significant inhibition zone against Staphylococcus vitulinus (24.67 ± 0.577 mm) and low MIC (0.097 μg mL −1 ) against S. vitulinus . The antibiofilm activity of Ag0.75 @ZFO NPs was the highest, recorded as 97.3% for S. aureus and 95.25% for Enterococcus columbae . In the case of UV exposure, bacterial growth reached the lowest grade. Finally, it was seen that the amount of cellular protein released from bacterial cells is directly proportional to the concentration of Ag0.75 @ZFO NPs, which clearly explains the formation of pits in the cell membrane. The synthesized nanocomposites may find an application after mixing with operating room paints to reduce the harmful effect of pathogenic microbes and, therefore, eliminate bacterial contamination.